"W Drodze". Głos polskiej emigracji na Bliskim Wschodzie podczas II wojny światowej (od początków czasopisma po powstanie warszawskie) = "W Drodze" ["En Route"] - the voice of Polish emigration in the Middle East during World War II (from the beginning of the magazine to the Warsaw Uprising) - Stańczak, Wioletta (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
"W Drodze" ["En Route"] was a magazine published in Jerusalem from 1943 to 1946 by the Polish émigré circles, particularly by the Polish soldiers and refugees stationing in the Middle East during World War II. It emerged during the challenging wartime period when many Poles fund themselves far from home, serving as both a bridge to their homeland and a platform for the exchange of thoughts and ideas. The magazine covered the topics related to the Polish culture, history, and literature, as well as everyday life and the unique challenges of life in exile. The articles, essays, poetry, and literary reviews reflected the spiritual and intellectual character of the Polish émigré community at that time, sustaining national unity in a distant corner of the world.
Keywords: "W Drodze" - czasopismo; Powstanie Warszawskie - 1944; idea pisma; bohaterowie; polski emigrant; "W Drodze" ["En route"] - magazine; Warsaw Uprising; idea of the magazine; heroes; polish emigrants